2018
DOI: 10.5888/pcd15.170352
|View full text |Cite
|
Sign up to set email alerts
|

State-Level Guidance and District-Level Policies and Practices for Food Marketing in US School Districts

Abstract: State agencies play a critical role in providing school districts with guidance and technical assistance on school nutrition issues, including food and beverage marketing practices. We examined associations between state-level guidance and the policies and practices in school districts regarding food and beverage marketing and promotion. State policy guidance was positively associated with districts prohibiting advertisements for junk food or fast food restaurants on school property. Technical assistance from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies have evaluated similar regulations within specific settings. Although most US school districts require or recommend prohibiting advertising of unhealthy foods or soft drinks in schools, 37 only 2 local jurisdictions in California proposed or regulated promotion of unhealthy foods through free toys or other incentives as of 2011. 35 Zoning to prohibit fast-food outlets has been limited; our results mirror a cross-sectional survey of all US LHDs where 1% reported involvement in policy to limit fast-food outlets, 25 and an inventory found that only 77 US local jurisdictions had proposed or adopted such land use policies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have evaluated similar regulations within specific settings. Although most US school districts require or recommend prohibiting advertising of unhealthy foods or soft drinks in schools, 37 only 2 local jurisdictions in California proposed or regulated promotion of unhealthy foods through free toys or other incentives as of 2011. 35 Zoning to prohibit fast-food outlets has been limited; our results mirror a cross-sectional survey of all US LHDs where 1% reported involvement in policy to limit fast-food outlets, 25 and an inventory found that only 77 US local jurisdictions had proposed or adopted such land use policies.…”
Section: Discussionmentioning
confidence: 99%